Kinematic behavior of solid particles in enclosed lid-driven cavity using CIP method - Ali Akbari, Sheldareh (2012)
The Cubic Interpolated Pseudo-Particle Navier Stokes equation (CIP-NSE) was applied to investigate the two-dimensional laminar square lid driven cavity flow of water at Reynolds number 1000. CIP-NSE scheme was used to solve hyperbolic term of the vorticity transport equation. In the CIP-NSE, the gradient and the value of the vorticity at the nodes is determined and the stream function is then determined using the vorticity equation. It is discovered that the numerical simulation of CIP-NSE provided a very good agreement with the established benchmark results by previous researchers. The Runge-Kutta method has been used to calculate the velocity and position of the particle with the effects of Drag force and Gravitational forces. The hard sphere model has been applied to show the collisions effect on particles in the Lid-Driven cavity. The main result achieved from the investigation is that, as the density of particles increases the number of particles collision in first seconds of the investigation decreases and the number of particles settled on the floor of the cavity increases, so for higher density of particles there have been large number of particles settlement on the floor and the collision at starting of investigation decrease as the particles moves slower, and for the lighter particles and lower density of particles number of collision at starting of investigation in more as the particles are lighter and move faster but the particles settlement on the floor of cavity are less in compare to higher density of particles. All simulation have been done for four different density of particle which are 1000, 1200, 1700, and 2000 (kg/m³).